1. f(x)=c,f’(x)=( )。
A: 0
B: c
C: 1
D: c'
A: 0
B: c
C: 1
D: c'
举一反三
- 已知f(x+1)=-f(x)且f(x)=1,(-1<x<0)0,(0≤x<1),则f(3)=( ) A: -1 B: 0 C: 1 D: 1或0
- 1.设$f(x)$在区间$I$内连续且$f(x)\ne 0$,若${{F}_{1}}(x)$,${{F}_{2}}(x)$是$f(x)$的两个原函数,则在区间$I$内( ). A: ${{F}_{2}}(x)\equiv {{F}_{1}}(x)$ B: ${{F}_{1}}(x)\equiv C{{F}_{2}}(x)$ C: ${{F}_{1}}(x)+{{F}_{2}}(x)\equiv C$ D: ${{F}_{2}}(x)-{{F}_{1}}(x)\equiv C$
- 下列函数在x=0处连续的是( ) A: f(x)=-1,(x≤0)x-1,(x>0) B: f(x)=lnx C: f(x)=|x|x D: f(x)=-1,(x>0)0,(x=0)1,(x<0)
- 设f(x),g(x)是恒不为零的可导函数,且f’(x)g(x)-f(x)g’(x)>0,则当0<x<1时()。 A: f(x)g(x)>f(1)g(1) B: f(x)g(x)>f(0)g(0) C: f(x)g(1)<f(1)g(x) D: f(x)g(0)<f(0)g(x)
- 设f(x)=x|x|,则f′(0)=() A: 1 B: -1 C: 0 D: 不存在